Perceived Stress, Resilience, and Anxiety Among Pregnant Chinese Women During the COVID-19 Pandemic: Latent Profile Analysis and Mediation Analysis - Luo, Zheng; Shen, Yaqing; Yuan, Jiajia; Zhao, Yifan; Liu, Zhengkui; Shangguan, Fangfang (Frontiers in Psychology, 2021)
Objective: The COVID-19 pandemic has posed a major threat to the mental health of pregnant women. This study aimed to characterize the patterns of perceived stress in pregnant Chinese women during the COVID-19 pandemic, to examine the profile differences on anxiety and resilience, and to investigate whether the differences in these profiles on anxiety were mediated by resilience. Methods: A sample of 2116 pregnant Chinese women who participated in online crisis interventions completed an online self-reporting questionnaire assessing their demographic characteristics, perceived stress, resilience and anxiety from February 28 to April 26, 2020. Results: Latent profile analysis (LPA) on two stress dimensions (perceived helplessness and perceived self-efficacy) indicated four perceived stress profiles: adaptive (33.7% of the sample), resistant (44.6%), insensitive (19.1%) and sensitive (2.6%). The women with adaptive and insensitive profiles both had the lowest levels of anxiety, while those with the resistant profile had the lowest levels of resilience. Multicategorical mediation analysis showed that resilience partially mediated the differences in the pregnant women’s anxiety between the adaptive/insensitive and resistant profile. Conclusion: This study showed the heterogeneity in the perceived stress patterns of pregnant women during the COVID-19 pandemic, revealing the internal mechanisms of pregnant women’s anxiety using a person-centered approach, and provided initial evidence guiding the development of differentiated stress interventions to alleviate pregnant women’s anxiety during the pandemic.